Pulse energy sustainability of a burst mode closed-cycle pulsed HF chemical laser. (29th January 2019) - Tao, Mengmeng; Shen, Yanlong; Zhu, Feng; Huang, Chao; Ma, Lianying; Chen, Hongwei; Luan, Kunpeng; Huang, Ke; Feng, Guobin; Ye, Xisheng
Abstract: Pulse energy sustainability of a burst mode closed-cycle pulsed HF laser is investigated with a simple theoretical model considering gas replenishment and chemical scrubbing. The effects of reactant gas consumption and de-excitation of excited HF by ground state HF are studied quantitatively. Also, experiments are carried out for comparison and validation. Simulation and experiments show that, in the burst mode operation, the energy loss caused by gas consumption is about 0.06–0.12 mJ per pulse while that induced by the de-excitation process is about 0.22–0.29 mJ per pulse, demonstrating that chemical scrubbing should play a more important role in the energy preservation of non-chain pulsed HF lasers.